Gestaltic blocking, psychopathological traits and coping styles in drug user ́s family - Calderón González , Francisco Antonio (Consorcio de Universidades Mexicanas A.C., 2018)
The consumption of drugs affects not only those who consume them, but also those who live with the consumer. The purpose of this study was to collect data of the physical and psychological effects of family members living with a drug user. Contact interruption, stemming from Gestalt psychotherapy theory, utilized by family members and their effect on their coping was investigated. Using a quantitative cross-sectional design, two different groups (n = 30 each), were evaluated. The first group was composed of drug user family members and the second included family members without drug users. Three instruments previously validated in Mexican samples were used: the Symptom Scale (SRT), The Castanedo-Munguia Scale of Contact Interruptions, and the Coping Questionnaire (CQ). These instruments showed high reliability and results demonstrated significant correlations, especially between contact interruption and psychopathology symptom. Additionally, there were significant differences on psychological symptoms between the two groups. These results may inform the design of novel psychotherapeutic intervention that incorporate elements investigated in this study.